ON JULLIEN’S REPLY TO BILLETE R’S CRITIQUE: MOVING BEYOND THE CARTESIAN COGITO AS A METHODOLOGICAL CONCERN - Carpanini, Francesco (Problemos, 2016)
Francois Jullien’s research, which encompasses European philosophy and sinology, has been questioned by the sinologist Jean Francois Billeter in a specific publication that triggers the reply of the former. I delve into Jullien’s reply with reference to the contingency of European thought, whose Cartesian cogito represents somehow the very point of divergence in the debate. The main goal of this paper is to clarify how the sentence I think, therefore I am turns out to be a fundamental methodological concern in Jullien’s research. His reflection about the Cartesian cogito leads him to question the possibility of a pure act of thinking in order to explore how European thought and Chinese thought exploit the diverse features of their languages as intellectual resources.